“If it’s necessary, it has to be done. And that’s for the physician to decide, not me.” Imaging techniques in monitoring routines in coronary heart disease and post-stroke patients: A qualitative interview study from the patients’ perspective - Laura Rink; Julia Heisig; Ciara Elisa Fink; Carolin Gonschorek; Veronika van der Wardt; Annika Viniol; Thomas Kühlein; Susann Hueber (PLoS ONE, 2025)
Background Chronic conditions such as coronary heart disease and stroke impose a significant burden on individuals and healthcare systems. Regular monitoring, including imaging techniques such as echocardiography and carotid duplex sonography, is used in follow-up care to detect disease progression and guide treatment decisions. Although these procedures are thought to provide clinical benefit, evidence-based guidelines provide limited recommendations for their routine use. This raises concerns about potential overdiagnosis, unnecessary healthcare costs and the psychological impact of frequent medical examinations. This study explores how patients with coronary heart disease and post-stroke experience and perceive these monitoring practices, focusing on their expectations, emotional responses and perceived benefits. Methods A qualitative study was conducted using semi-structured interviews with patients who had undergone echocardiography or carotid duplex sonography within the past three years. Participants were recruited in two regions in Germany. Interviews were transcribed and analysed following Braun and Clarke’s reflexive thematic analysis approach. Results Fourteen patients were interviewed. Participants generally found monitoring to be beneficial and reassuring. They expressed confidence in their physicians’ recommendations and felt that the frequency of monitoring was appropriate. Patients left decisions about their regular monitoring entirely to their physicians. A hypothetical reduction raised concerns about the rationing of care. In addition, monitoring was perceived as influencing therapeutic decisions, reinforcing the perceived need for monitoring. Conclusions Patients’ positive attitudes towards monitoring are shaped by their perception of medical necessity, which is primarily influenced by their physicians. Given patients’ reliance on physician advice, the responsibility for refining monitoring strategies lies primarily with physicians, who should critically assess indications to avoid unnecessary investigations.